Dakwah Islam di Era Multimedia (Studi atas Minat Para Da’i IKMI Kota Pekanbaru Menggunakan Media Cetak Sebagai Media Dakwah) - Zulkarnain Zulkarnain (Jurnal Dakwah Risalah, 2013)
preaching using print media requires writing talent because it is a means of communication posts. Many preachers have capability to speak greatly in podium but not able to put it in an essay. This paper examined the interest of IKMI’s preachers in preaching using the multimedia. Results of research showed that interest of IKMI’s using multimedia is still lacking. The majority of them are less interested in delivering propaganda through print media. They would rather deliver lectures or preaching to the conventional method. They do this because there are many of them who do not have the ability to write.